Implementasi Pencak Silat Setia Hati Teratai Berbasis Etnopedagogis Sebagai Penguat Karakter Profil Pelajar Pancasila - Purnamasari, Asri Indah; Widodo, Wahono; Istiq’faroh, Nurul (CV. Kurnia Grup, 2024)
Education plays an important role in the inheritance of values and culture, especially amidst the currents of globalization that can now erode local cultures and integrate local wisdom values, including in the character education of students. One form of culture that can be implemented in character education is pencak silat, specifically the Setia Hati Teratai school of pencak silat. This research aims to analyze the ethnopedagogical implementation of Pencak Silat Setia Hati Teratai as a character strengthener of the Pancasila Student Profile among students. The type of research uses a descriptive qualitative approach, emphasizing the reduction, display, and analysis of data from various literatures related to character education and culture. The subjects of the research involve trainers of Setia Hati Teratai Pencak Silat, teachers who teach in schools, and students who apply local wisdom in their learning. The research results show that the training and philosophy in Pencak Silat Setia Hati Teratai support the instillation of values such as mutual cooperation, noble character, independence, and global diversity, as well as the overall values included in the Pancasila Student Profile. Through an ethnopedagogical approach, pencak silat not only functions as a physical activity but also as a medium for character education that aligns with Pancasila. Thus, Pencak Silat Setia Hati Teratai has great potential to be developed in culture-based character education, contributing to the formation of a young generation that is characterized, nationalistic, and tolerant of diversity.